(3eONd Gdi Yde GdPQI (B:s (3HMK Ydej (B/ s - (3jejf,jhSa,s ((3HjQhJ(B[(3dHfGf(B] :s (3OGQ GHYGO ddWHGYI hGdfTQ hGdJhRjY,s, 1982)
(3gPG GdcJGH gh GdGhd aj GddZI GdYQHjI Yf Yde GdPQI,hgh LRA aj SdSdI (B"(3ef GdPQI Gdi GdeLQI(B"(3GdJj JLeY Hjf GdHMK GdYdej GdGcGOjej GdeQLYj hHjf SghdI GdhUhd Gdi ChSY hSW ef GdbQGA(B.s
(3GdYfhGf Ydi GdZdGa (B: (3eONd Gdi Yde GdPQI(B.s
(3jJVef edGMb(B.s
(3jJVef bGFeI HGdeUWdMGJ GdYdejI,YQHj aQfSj GfcdjRj,UaMI(B189-192.s
(3jJVef GQLGYGJ HHdjhLQGajI(B.s
(3jJVef bGFeI HYfGhjf cJH SdSdI ef GdPQI Gdi GdeLQI(B.s
Keywords: (3GdPQGJs